Performance of a deep learning tool to detect missed aortic dilatation in a large chest CT cohort - Pradella, Maurice; Achermann, Rita; Sperl, Jonathan I.; Kärgel, Rainer; Rapaka, Saikiran; Cyriac, Joshy; Yang, Shan; Sommer, Gregor; Stieltjes, Bram; Bremerich, Jens; Brantner, Philipp; Sauter, Alexander W. (Frontiers in Cardiovascular Medicine, 2022)
Purpose Thoracic aortic (TA) dilatation (TAD) is a risk factor for acute aortic syndrome and must therefore be reported in every CT report. However, the complex anatomy of the thoracic aorta impedes TAD detection. We investigated the performance of a deep learning (DL) prototype as a secondary reading tool built to measure TA diameters in a large-scale cohort. Material and Methods Consecutive contrast-enhanced (CE) and non-CE chest CT exams with ‘normal’ TA diameters according to their radiology reports were included. The DL-prototype (AIRad, Siemens Healthineers, Germany) measured the TA at nine locations according to AHA guidelines. Dilatation was defined as >45mm at aortic sinus, sinotubular junction (STJ), ascending aorta (AA) and proximal arch and >40mm from mid arch to abdominal aorta. A cardiovascular radiologist reviewed all cases with TAD according to AIRad. Multivariable logistic regression (MLR) was used to identify factors (demographics and scan parameters) associated with TAD classification by AIRad. Results 18’243 CT scans (45.7% female) were successfully analyzed by AIRad. Mean age was 62.3±15.9 years and 12’092 (66.3%) were CE scans. AIRad confirmed normal diameters in 17’239 exams (94.5%) and reported TAD in 1’004/18’243 exams (5.5%). Review confirmed TAD classification in 452/1’004 exams (45.0%, 2.5% total), 552 cases were false-positive but identification was easily possible using visual outputs by AIRad. MLR revealed that the following factors were significantly associated with correct TAD classification by AIRad: TAD reported at AA (odds ratio (OR): 1.12, p<0.001) and STJ (OR: 1.09, p=0.002), TAD found at >1 location (OR: 1.42, p=0.008), in CE exams (OR: 2.1-3.1, p<0.05), men (OR: 2.4, p=0.003) and patients presenting with higher BMI (OR: 1.05, p=0.01). Overall, 17’691/18’243 (97.0%) exams were correctly classified. Conclusions AIRad correctly assessed the presence or absence of TAD in 17’691 exams (97%), including 452 cases with previously missed TAD independent from contrast protocol. These findings suggest its usefulness as a secondary reading tool by improving report quality and efficiency.